Seismic Response of Steel Fibre Reinforced Concrete Beam-Column Joints - Abbas, Ali A.; Sharifah Maszura, Syed Mohsin; Cotsovos, Demetrios M. (Elsevier Ltd, 2014)
The present research work aims to investigate numerically the behaviour of steel fibre reinforced concrete beamâcolumn joints under seismic action. Both exterior and interior joint types were examined and 3D nonlinear finite element analyses were carried out using ABAQUS software. The joints were subjected to reversed-cyclic loading, combined with a constant axial force on the column representing gravity loads. The joints were initially calibrated using existing experimental data â to ascertain the validity of the numerical model used â and then parametric studies were carried out using different steel fibre ratios coupled with increased spacing of shear links. The aim was to assess the effect of introducing steel fibres into the concrete mix in order to compensate for a reduced amount of conventional transverse steel reinforcement and hence lessen congestion of the latter. This is particularly useful for joints designed to withstand seismic loading as code requirements (e.g. Eurocode 8) lead to a high amount of shear links provided to protect critical regions. The spacing between shear links was increased by 0%, 50% and 100%, whilst the fibre volume fraction (Vf) was increased by 0%, 1%, 1.5%, 2% and 2.5%. Potential enhancement to ductility, a key requirement in seismic design, was investigated as well as potential improvements to energy absorption and confinement. The work also examined key structural issues such as strength, storey drift, plastic hinges formation and cracking patterns.